2005
DOI: 10.1002/elsc.200420056
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(3-hydroxybutyrate-co-4-hydrobutyrate) with a Target Mole Fraction of 4-Hydroxybutyric Acid Units by Two-Stage Continuous Cultivation ofDelftia acidovorans P4a

Abstract: Delftia acidovorans P4a (DSMZ 10474) was grown in mineral medium on acetic acid at pH 8.0 without an additional supply of nutrients like yeast extract or polypeptone. Using acetic acid and γ‐butyrolactone (GBL), copolymers with a 4HB content from 2–90 mol % were detected in batch experiments, depending on the ratio of the both carbon substrates. Due to the different consumption rates of the individual carbon substrates a multitude of different target mole fractions were difficult to produce by fed‐batch fermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Preparation of PHA substrates P(3HB) and P(3HB-4HB) with 10.8% 4HB fraction were obtained from a fermentation process as described in [8]. Both polymers were solvent re-precipitated using chloroform (Fluka, Deisenhofen, Germany) and deionised water prior usage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of PHA substrates P(3HB) and P(3HB-4HB) with 10.8% 4HB fraction were obtained from a fermentation process as described in [8]. Both polymers were solvent re-precipitated using chloroform (Fluka, Deisenhofen, Germany) and deionised water prior usage.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these copolymers, degrading to intermediates occurring naturally in the body, are one of the most suitable PHA for implantable medical scaffolds [7]. In our recent work fermentation strategies were developed which produced poly(3-hydroxybutyrateco-4-hydroxybutyrate) (P(3HB-4HB)) with target mole fractions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Also here, D used for the first stage was close to the biological maximum determined by the strain's µ max. (0.21 1/h), whereas the second stage was operated at a D of 0.16 1/h; 1.06 g/(L h) of poly(3-hydroxyhexanoate-co-3-hydroxyoctanoate) were reported for the volumetric productivity, with cells containing 0.63 g/g of the mcl-PHA [137]. Moreover, P. putida GPo1 was also cultivated by Hartmann and colleagues in a two-stage chemostat system consisting of two chemostats linked in sequence with two different substrates (octanoic acid in the first and 10-undecenoic acid in the second stage).…”
Section: Two-stage Chemostats Under Strict Sterility Precautionsmentioning
confidence: 99%
“…D was adjusted to 0.2 1/h for the first, and, in order to provide higher τ, to 0.06 1/h for the second CSTR. It was demonstrated that the optimum PHA productivity and the pre-definition of 4HB contents in PHA can be achieved by triggering the ratio between acetate and GBL [ 60 ]. Similar to the findings described before for the substrate system butanoate and pentanoate [ 43 ], also this example of application of inhibiting substrates (acetate and GBL) demonstrates the viability of continuous production mode especially to conveniently supply the cells with the required amounts of substrates without exceeding inhibiting concentration levels.…”
Section: Two-stage Continuous Systems With Pure Culturesmentioning
confidence: 99%